Kualitas Papan Semen Partikel Serbuk Gergaji Kayu Meranti Merah (Shorea leprosula Miq.): Red Meranti Wood (Shorea leprosula Miq.)Sawdust Particle Cement Board Quality - Ludang, Yetrie; Luhan, Gimson; Fauzi, Fuad; Herianto, Herianto; Jaya, Herry Palangka; Joni, Herwin; Triyadi, Antonius; Sinulingga , Merinda Br (JURNAL HUTAN TROPIKA, 2025)
Research has demonstrated the treatments using sawdust–cement ratios of A1 (1:1.5), A2 (1:2), A3 (1:2.5), and A4 (1:3) in the manufacture of red meranti wood particle cement boards based on the SNI 03-2105-2006 standard. The results showed that the physical and mechanical properties of red meranti sawdust cement boards met the standards for moisture content, density, and thickness swelling. However, the modulus of elasticity (MoE) and modulus of rupture (MoR) did not meet the SNI 03-2105-2006 requirements. The analysis of variance indicated that the sawdust–cement ratio treatments had no significant effect on moisture content, density, and thickness swelling, but had a significant effect on the modulus of elasticity (MoE) and modulus of rupture (MoR), with the best treatment being A1 (1:1.5). The quality of the red meranti sawdust cement board falls under the ordinary type 1 particle cement board with a thickness of 13 mm and medium density, and is therefore recommended for non-structural uses such as interior partition walls, ceilings, decorative purposes, and tabletops.